Technology diplomacy for the digital era - Muñiz, Manuel (CIDOB (Barcelona centre for international affairs), 2023)
The huge technological advances in recent decades have a fundamental international corollary: they make technology a new field of diplomacy. The deployment of an effective tech diplomacy will be a decisive factor of success in the 21st century. A state’s capacity to advance its security and economic interests,as well as its normative interests linked to values and principles,will depend on it. This diplomacy will require new instruments in foreign ministries,the development of new skills among the diplomatic profession,as well as devising specific strategies and road maps. Over time,a whole architecture of tech governance will emerge,linked both to privacy and data management and to monitoring systems and the use of artificial intelligence (AI) in multiple spaces,including defence. © 2023
[Diplomacia tecnológica para la era digital]
Keywords: Digital era; Diplomacy; Economics; Global order; Security; Technology; ODS 9 - Industria, innovación e infraestructura